Facility Registration and Initial Regulatory Compliance Activities for Acidified Food and Low-Acid Canned Food Processors in Florida - Matthew Krug; Soohyoun Ahn (EDIS)
Food businesses are subject to a wide range of regulatory requirements. Food entrepreneurs who want to produce and sell acidified foods or low-acid canned foods must abide by specific FDA regulations. This new 3-page document intends to clarify the initial steps food entrepreneurs must implement to comply with these regulations. This factsheet is one in a Food Entrepreneurship in Florida series, which assists beginning and established food entrepreneurs by providing them information on topics highly relevant to starting and running a food business: regulations, safety, labeling, processing, and marketing. Written by Matthew Krug and Soohyoun Ahn, and published by the UF/IFAS Food Science and Human Nutrition Department, February 2019. http://edis.ifas.ufl.edu/fs318